Emerging technologies in the possession and carrying of weapons for civil use in Ecuador - Acurio Hidalgo, German Fabricio; Acurio Hidalgo, José Luis; Poso Velez, Esteven Antonio; Loayza Zambrano, Genesis Ariana (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This study addresses the controversial authorization of the possession and carrying of weapons by civilians in Ecuador, and the impact of emerging technologies in the field of security and defense. Ecuadorian legislation allows citizens to carry weapons under strict requirements, seeking to balance self-defense with the prevention of armed violence. In the context of rising crime, this article explores how emerging technologies are redefining the operational capabilities of both armed forces and non-state actors. AI improves precision and efficiency in military operations, while 3D printing enables rapid, customized production of weapons components, although it poses regulatory challenges. The use of drones has increased significantly, offering benefits in surveillance and logistics, but also significant risks in illicit activities. The research was carried out through a qualitative approach, using documentary analysis, case studies and statistical data from sources. It should be emphasized that security in Ecuador cannot depend solely on the authorization of the carrying of weapons, but requires an integrated approach that addresses the underlying causes of violence. Training in the responsible use of new technologies and public-private collaboration are essential to take advantage of their benefits and improve security and operational efficiency in the country.